The impact of independence, auditors' competence and information technology usage on internal audit quality: empirical evidence from Chinese commercial banks - Mohammed Shah, Sabarina; Zhang, Chi; Ngalim, Siti Manisah; Lau, Yeng Wai (Virtus Interpress, 2024)
The purpose of this article is to study the primary influencing factors of internal audit quality (IAQ) in Chinese commercial banks (CCBs). To achieve this, we first conducted a search on China National Knowledge Infrastructure (CNKI) and identified 64 conceptual articles related to IAQ in CCBs. It is generally believed that the competence of internal auditors (COMP), the independence of internal audit (IND), and information technology usage (ITU) are key factors in improving the quality of internal audits. Secondly, to deeply analyze the impact of these three key factors, we conducted a questionnaire survey in CCBs. The questionnaire data verified that the impact of these three factors on IAQ is significant through the partial least squares structural equation modeling (PLS-SEM) method.